Substrate fields modulation with defected ground structure: A key to realize high gain, wideband microstrip antenna with improved polarization purity in principal and diagonal planes. Issue 2 (20th November 2015) - Chakraborty, Subhradeep; Chattopadhyay, Sudipta
ABSTRACT: Rectangular microstrip patch antenna with circular headed dumbbell shaped defect in ground plane has been studied experimentally for concurrent improvement in its gain, bandwidth and polarization purity in principal and 45° diagonal planes. Around 9–9.5 dBi peak co polarized (CP) gain, 22% impedance bandwidth along with minimum 19–20 dB of CP‐cross polarized (XP) isolation in both principal and 45° diagonal plane are achieved with the present structure. These observed improvements in results from present antenna are justified with physical insight. The present structure is simple and easy to manufacture. The geometry of the defect in ground plane has been shaped judiciously to modulate the fields beneath the patch efficiently for simultaneous improvement of the three parameters. Very close mutual agreement between simulation and measure results are revealed. The present investigation provides an insightful, visualization‐based understanding of concurrent improvement of all these parameters. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:174–181, 2016.